Accuracy of points of cartographic projection of orthophotos obtained with remotely piloted aircraft (RPA) - Alves Junior, Agostinho Prado; Gomes, Luciano Nardini [UNESP] (Univ Federal Espirito Santo, 2022)
This study evaluated three orthophotos, generated from aerial surveys configured at 80 m, 100 m and 120 m in height with multirotor RPA, model Phantom 4 Pro from the company DJI coupled to Complementary Metal Oxide Semiconductor (CMOS) sensor of 1 inch of 20 megapixels, on a property located on the banks of Rodovia Agostinho Ducci (PR-218), rural area of the municipality of Sao Sebastiao da Amoreira in the state of Parana, Brazil. Of remotely piloted aircraft (RPA) using support points in the georeferencing of images. Accuracy was assessed based on trend and precision analysis, and the results were classified according to the Cartographic Accuracy Standard for Digital Cartographic Products (PEC-PCD) for a scale of 1:1.000.
Keywords: Orthophoto; Digital Elevation Model; Tophografy